ISAR Imaging of Ship Target with Complex Motion Based on New Approach of Parameters Estimation for Polynomial Phase Signal. (17th March 2011) - Wang Wang, Yong Yong; Jiang Jiang, Yi-Cheng Yi-Cheng
Abstract : ISAR imaging of ships at sea with significant motion results in the Doppler frequency shift for the received signal is time-varying, which will deteriorate the ISAR image quality for the Range-Doppler (RD) algorithm. In this paper, the received signal is modeled as a multicomponent cubic phase signal (CPS), and a new method for estimating the parameters of CPS based on the integrated high-order matched phase transform (IHMPT) is proposed. This algorithm is simpler and more computational efficient than some of other parameters estimation algorithms proposed previously. Then, combined with the Range-Instantaneous-Doppler (RID) technique, the high quality instantaneous ISAR images can be obtained. The results of simulated and measured data are provided to demonstrate the effectiveness of the new method proposed.